Comparison of Tacrolimus Starting Doses Based on CYP3A5 Phenotype or Genotype in Kidney Transplant Recipients. (December 2019) - Largeau, Bérenger; Guellec, Chantal Barin-Le; Longuet, Hélène; Lesne, Philippe; Bouvarel, Antoine; Préteseille, Laura; Marquet, Pierre; Halimi, Jean-Michel; Büchler, Matthias; Gatault, Philippe; Noble, Johan
Background: Selection of expected phenotypes (ie, expressers/non-expressers) is currently used in CYP3A5*3 genotype-based tacrolimus dosing. The authors assessed whether a dosing regimen based on the 3 CYP3A5 genotypes may reduce the occurrence of inadequate exposure. Methods: Tacrolimus whole blood trough levels ( C 0 ) were retrieved from a retrospective cohort of 100 kidney transplant recipients treated with a starting dose of 0.15 (non-expressers) or 0.30 (expressers) mg/kg/d. The authors evaluated the occurrence of overexposures (12 < C 0 < 20 ng/mL) or toxic concentrations ( C 0 ≥ 20 ng/mL). These results were used to set up a new strategy based on the 3 distinct CYP3A5 genotypes, which relevance was evaluated in a prospective cohort of 107 patients. Results: In the retrospective cohort, non-expressers exhibited frequent overexposure (63.6%) or toxic C 0 (20.8%). Among expressers, none of the homozygous *1 carriers exhibited overexposure contrary to 25% of the heterozygotes. Based on these results, new tacrolimus starting doses were set at 0.10, 0.20, and 0.30 mg/kg/d for CYP3A5*3/*3, CYP3A5*1/*3, and CYP3A5*1/*1 genotypes, respectively. Tacrolimus overexposure was reduced in the CYP3A5*3/*3 group (63.6% vs 40%, P = .0038). None of the heterozygous patients exhibited toxic tacrolimus C 0 . Clinical outcomes were not different between the 2 periods, whatever the genotype. Our results indicate that the best tacrolimus exposure was obtained for doses of 0.10, 0.20, and 0.20 mg/kg/d for CYP3A5*3/3, CYP3A5*1/*3, and CYP3A5*1/*1, respectively. Conclusions: Our results confirm that selecting tacrolimus dosing regimen according to the expected phenotype is appropriate, but that lower than currently recommended doses may be preferable.